Environmental assessment of the quality of surface waters in the upper reaches of the Pripyat basin in Ukraine using different methods - Khilchevskyi, Valentyn K.; Netrobchuk, Iryna M.; Sherstyuk, Natalya P.; Zabokrytska, Myroslava R. (My University, 2022)
The aim of the study is to assess the quality of river waters in the upper reaches of the Pripyat River in Ukraine using two methods of environmental assessment of surface water quality in the relevant categories and to identify the effectiveness of these methods. The main factors influencing the water quality of the upper reaches of the Pripyat River in the Volyn region in the absence of large industrial and municipal enterprises in the basin are: the location of quite large rural settlements on the river bank, many of which do not have centralized drainage; the impact of the water of the Turiya River, which is polluted by domestic wastewater in Kovel; development of farms during unsatisfactory condition of the reclamation network; increase of anthropogenic pressure due to construction and plowing of the river. In order to perform ecological assessment of river water quality in the upper reaches of the Pripyat River, the Methodology of Ecological Assessment of Surface Water Quality by Relevant Categories approved in 1998 in Ukraine (Methodology-1998) and the modernized version of this methodology developed in 2012 were used by Ukrainian Research Institute of Environmental Problems (methodology-2012). The second method contains improved evaluation method of water quality according to the criteria of salt composition of water, taking into account the hydrochemical zoning of Ukraine. Analysis of the results obtained by two methods showed that the average annual salt composition (I1) quality of river waters of the upper Pripyat mainly corresponded to the 1st, 4th categories of I, III classes (“excellent”, “satisfactory” by condition, and “very clean”, “slightly contaminated” by the degree of contamination). According to troph-saprobiological (I2) indicators – the 4th category of class III water quality (“satisfactory” by condition and “slightly polluted” by the degree of pollution). According to the indicators of specific substances of toxic water (I3) –the 3rd, 5th category II, III classes of water quality (“good”, “mediocre” by condition and “fairly clean”, “moderately polluted” by the degree of contamination). According to the average annual values of integrated ecological indices (IE), obtained by two methods, the water quality of the upper Pripyat was characterized by the 3rd, 4th categories of II, III classes (“good”, “satisfactory” in condition and “sufficient”, and “clean”, “slightly contaminated” by the degree of contamination). The results of the assessment of the surface water quality of the upper reaches of the Pripyat River by two methods showed that the requirements of the method-2012 are higher to the salt composition of water than in the method-1998. According to this method, water quality was characterized by a worse class (III) compared to the method of 1998, according to which the quality of river waters in the upper reaches of the Pripyat corresponded to class I. Thus, the method-2012 sets stricter requirements for environmental assessment of river water quality, which can make it a more effective mechanism in the field of water protection.
Keywords: river headwaters; water quality; ecological assessment; methodology; index; Pripyat; Volyn region; Ukraine